(untitled) (Dhaka University Journal of Science, 2018)
Tropical cyclones (TCs) over Bay of Bengal (BoB) have significant socio-economic impacts on the countries bordering the BoB. In this study, we have examined the structure and thermodynamic features of the TC Hudhud (7th -14th October, 2014) using WRF model. Simulated outputs are in good agreement with the available observations of India Meteorological Department and Joint Typhoon warning Center. At maximum intensity stage, the system’s horizontal size is found around 690 km. Wind and vorticity distributions capture the circulation of the system very well. Most strong winds of 60 ms−1 are extended vertically from 850 hPa to about 700 hPa. Simulation has shown intensification of the system above 200 hPa with wind speed of about 30ms−1. Relative humidity of the order of 90 % is found up to 400 hPa. Dhaka Univ. J. Sci. 66(1): 79-86, 2018 (January)